Pengembangan Aplikasi Pembelajaran Akidah Akhlak Untuk Meningkatkan Pemahaman Siswa Berbasis Web - Latifah Latifah; Nurlaila Adiningsih (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The lack of knowledge about moral aqidah causes low awareness of parents about the importance of knowledge of moral aqidah for children. Because actually the moral creed is very important for children to behave and speak well in everyday life. This condition is exacerbated by the difficulty of parents in obtaining knowledge about moral beliefs. Even though in today's era, many children use technology such as gadgets, through gadgets, children can use the internet to learn about moral beliefs. From this background, the purpose of this research is to create a Web-Based Akidah Akhlak Learning website to introduce and educate Muslims in Indonesia about the importance of moral aqidah. The method of designing the Akidah Akhlak learning system uses the Development Life Cycle System. On the admin page, there are menus that can be accessed by admins, such as the home page view, material display, video display, practice questions display, and logout. On the user page display, there are menus that can be accessed by the user such as the homepage display, material display, practice questions display, video display and a display about containing an explanation of the moral aqidah learning and the profile of the creator of the moral aqidah learning website. This website was created in order to increase knowledge of moral beliefs. By applying blackbox testing and calculating the Likert scale, it can be concluded that the moral aqidah learning website is in accordance with what is desired by the maker of the user.